Importance of P53, Ki-67 expression in the differential diagnosis of benign/malignant phyllodes tumors of the breast - Ulku Kucuk; Umit Bayol; Emel Ebru Pala; Suheyla Cumurcu (Wolters Kluwer Medknow Publications, 2013)
Background: Conventionally growth pattern, stromal overgrowth, stromal cellularity and stromal mitotic activity are the main parameters in the grading of phyllodes tumors (PTs). Recent studies revealed that both p53 and Ki-67 expressions are correlated with grade of PTs of the breast. Expression of hormone receptors and overexpression/amplification of HER2 has been studied in PTs to discover the roles of these markers as new treatment modalities. Materials and Method: We studied 26 PT cases. Seventeen benign and nine malignant PTs were re-evaluated as regards stromal cellularity mitotic activity, p53/Ki-67 expression rates and the relation between these parameters. Estrogen receptor and progesterone receptor (ER, PR) positivity were determined by counting nuclear staining in five high-power fields. Also, the presence of any HER2 staining and staining patterns were documanted. Results: Stromal cellularity, mitotic rate, p53 and Ki-67 expression rates were all correlated with benign and malignant histologic subgroups (P = 0.000-0.001). Ki-67 and p53 expressions were statistically significantly correlated with histologic subgroups, stromal cellularity and mitotic rate (P < 0.005). ER and PR expressions in the epithelial component were not statistically significant between the two groups. HER2 showed different staining patterns in the epithelial component, and there was no staining in the stromal component. Conclusion: Ki-67 and p53 expression rates were statistically significantly correlated with grade of mammary PTs; therefore, they can be used in the determination of tumor grade, especially for the differential diagnosis of benign and malignant tumors. Malignant and benign tumors did not differ significantly in terms of hormone receptor and HER2 expression. HER2 expression showed different patterns in the epithelial component of the PTs.